The Effectiveness Of Hyperbaric Bupivacaine Administration On Hemodynamic Changes In Sectio Caesarea Patients - Habsah Jumma, Misbachul Hayati; Burhan, Asmat; Heri Susanti, Indri (Java Nursing Journal, 2024)
Background: Sectio Caesarea (SC) is a critical surgical intervention used to manage abnormal labor, addressing potential health risks for both mother and infant. Spinal anesthesia, frequently administered using hyperbaric bupivacaine, plays a crucial role in the procedure. Purpose: This study aimed to evaluate the impact of hyperbaric bupivacaine on hemodynamic parameters in SC patients at Kardinah Hospital, Tegal City. Methods: A pre-experimental design with a One-Group Pretest-Posttest approach was employed. The study utilized purposive sampling to include 67 SC patients, aged 18-40 years with a BMI >18.5. Hyperbaric bupivacaine was administered as part of the anesthesia protocol. Hemodynamic parameters, including systolic and diastolic blood pressure, pulse rate, mean arterial pressure (MAP), SpO2, and respiratory rate (RR), were measured before and after administration of the anesthetic. Results: Analysis revealed a statistically significant effect of hyperbaric bupivacaine on systolic and diastolic blood pressure, pulse rate, and MAP (p = 0.00). In contrast, no significant effects were observed on SpO2 (p = 0.34) or RR (p = 0.15). Conclusions: The administration of hyperbaric bupivacaine in SC patients resulted in significant hemodynamic changes, particularly affecting blood pressure, pulse rate, and MAP. However, it did not significantly alter SpO2 or RR. These findings underscore the importance of monitoring hemodynamic parameters during spinal anesthesia to ensure patient safety and optimal management during cesarean sections